Factors Causing Work Accidents in Public Transportation Drivers: A Cross-Sectional Study - Permayasa, Nayodi; Lastari, Asdi; Apripan, Rika; J. Hadi, Anto (Promotif : Jurnal Kesehatan Masyarakat, 2024)
Background: Driving safety is an important factor in driving, especially for public transportation drivers. However, work pressures such as time targets, economic demands, and overwork can increase the risk of accidents. To analyze the factors that cause work accidents in public transportation drivers in Padangsidimpuan. Methods: Type of observational research with a cross-sectional study design. This research was carried out in the city of Padangsidimpuan. The population and sample are all city transportation drivers, as many as 145. A research questionnaire was carried out for data collection. Sampling techniques with exhaustive sampling and data analysis using chi-square and logistic regression. Results: This study proved that the length of working hours (p=0.001), smoking habits (p=0.001), compliance with the use of driving safety equipment (p=0.001), and health status (p=0.001) were the factors causing work accidents in public transportation drivers. At the same time, the most significant variable is the length of working hours Exp. (B)= 42.691. Conclusion: This study concludes that most work accidents occur due to unsupportive driver factors. Based on these findings, it is recommended that it is important to monitor the driver's physical condition regularly, provide adequate rest guarantees, and pay attention to his health factors.